Epiphany in the wilderness : hunting, nature, and performance in the nineteenth-century American West - Jones, Karen R., 1972- (University Press of Colorado, 2015)
"Stories of grand adventure and hunting loomed large in the material and the imagined landscape of the nineteenth-century West. Jones explores social, political, economic, and environmental dynamics of hunting using performance as trail guide and production of a '"cultural ecology of the chase"' in art and taxidermy"--